2014
DOI: 10.1016/j.minpro.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Calcination and characterisation studies of a Brazilian manganese ore tailing

Abstract: This paper discusses the systematic analysis of the results of calcination as a function of size fraction performed on a sample of Brazilian silicate-carbonate manganese ore tailing at 800°C. The raw materials and the corresponding calcination products were analysed using several analytical techniques, including determination of density, specific surface area and porosity, chemical analysis and X-ray diffraction. The morphology and chemical composition of the calcination products were analysed by using scannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 14 publications
0
10
0
1
Order By: Relevance
“…The peak above 650 °C indicates transformation of Mn 2 O 3 into Mn 3 O 4 occurs [10]. In other study, manganese ore contains rhodonite and rhodochrosite which thermal decomposition of carbonate manganese occurs at 547.9 °C [2]. Thermal analysis used TGA/DSC as seen on Figure 3 showed the decomposition manganese ore from Sumbawa.…”
Section: Figure 2 Tga-dsc Curve Of Manganese Orementioning
confidence: 87%
See 1 more Smart Citation
“…The peak above 650 °C indicates transformation of Mn 2 O 3 into Mn 3 O 4 occurs [10]. In other study, manganese ore contains rhodonite and rhodochrosite which thermal decomposition of carbonate manganese occurs at 547.9 °C [2]. Thermal analysis used TGA/DSC as seen on Figure 3 showed the decomposition manganese ore from Sumbawa.…”
Section: Figure 2 Tga-dsc Curve Of Manganese Orementioning
confidence: 87%
“…Naturally, manganese ore can be found as pyrolusite (MnO 2 ), psilomelane (BaMn 9 O 16 (OH) 4 ), dan manganite (Mn 2 O 3 H 2 O), haussmannite (Mn 3 O 4 ), Rodhochrosite (MnCO 3 ), dan Rhodonite (MnSiO 3 ) [1]. Sometimes manganese ore are also found together with others minerals such as quartz, kaolinite, dolomite, cordierite [2], hematite and lithiophorite [3].Well-known methods to process manganese ore are pyrometallurgy, hydrometallurgy and biometallurgy. Pyrometallurgical is common processes which has some drawbacks such as high cost, energy consumption, less productivity and heavy pollution [3].…”
Section: Introductionmentioning
confidence: 99%
“…Manganese is the twelfth most abundant element in the earth's crust (0.096%), and appears mainly as pyrolusite (MnO2), rhodochrosite (MnCO3), rhodonite (MnSiO3), manganite (MnO (OH)) and alabandite (MnS) . Pereira et al (2014) showed that manganese is used in the cell and battery manufacturing industry, the coloring of ceramics, the catalysis of certain organic reactions. The manganese used in batteries and accumulators has the oxide form, mainly manganese dioxide (MnO2) obtained after calcination of manganese carbonate (MnCO3) from the chemical precipitation of a sulfate solution.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the roasting of pellets of copper concentrates with lime as a reagent to absorb the sulfur dioxide and prevent the emission of sulfur dioxide was investigated [13]. Furthermore, calcification roasting was performed in disposing manganese ore and extracting of Ni and Mo from carbonaceous shale etc [14,15]. However, the calcification roasting methodology of complex multimetallic sulfide copper concentrates containing large amounts of lead and iron has not been reported in any document, especially the leaching kinetics of the roasting products obtained by roasting calcified the complex ore in sulfuric acid solution has not been well documented.…”
Section: Introductionmentioning
confidence: 99%